Shared State Responsibility for Land-Based Marine Plastic Pollution - Tanaka, Yoshifumi (Transnational environmental law, 2023)
Plastic litter is introduced into the oceans from land-based sources located in many countries around the world. Marine plastic pollution may therefore be attributable to multiple states, resulting in shared state responsibility. This article discusses the issue of shared state responsibility for land-based marine plastic pollution by examining (i) primary rules of international law concerning the prevention of land-based marine plastic pollution; (ii) secondary rules of international law on this subject; and (iii) possible ways of strengthening the primary rules. It concludes that the barrier for the invocation of state responsibility may become higher in cases of shared state responsibility. Three cumulative solutions to this problem are proposed: elaborating the obligation of due diligence, strengthening compliance procedures, and interlinking regimes governing the marine environment and international watercourses.